(untitled) (Communication & Society, 2009)
This article presents the findings of a research carried out in 2008 to identify the actors and contents of mobile communication produced in Catalonia. Mobile communication, one of the most dynamic sectors of the global economy, is changing different aspects of social life, from relationship models to cultural production, distribution and consumer processes. The research draws a situation map, proposes a series of analytical categories and opens the field for more specific analysis of mobile communication in Catalonia in the future.